Hubungan antara Kepribadian Ekstraversi dan Kesepian dengan Kecenderungan Nomophobia pada Remaja - Ciptadi, Wenny Acnashinta; Selviana, Selviana (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This study aims to examine the relationship between extraversion personality and loneliness withthe tendency of nomophobia. The research respondents were teenagers in class XI and XII inSMA Annajah totaling 160 people using simple random sampling. Data analysis uses correlationbivariate which shows that there is a positive and significant relationship between personalityextraversion and the tendency of nomophobia, r = 0.336 and p 0.000 <0.05. There is a positiveand significant relationship between loneliness and the tendency of nomophobia with r = 0.019with p 0.01 <0.05. Based on multivariate correlation analysis shows that there is a positive andsignificant relationship between extraversion and loneliness with the tendency of nomophobiawith R = 0.344 and p = 0.000 <0.05 with the effective contribution of extraversion and lonelinessto the tendency of nomophobia by 11.8%. The rest is contributed by other factors not examined.